Resposta :
a) 4x²+12x+9
b) 16x²+56xy+49y²
c) 25a²+70a+36
a) (2x + 3)² = (2x)²+2(2x)(3)+(3)² = 4x²+12x+9
b) (4x + 7y)² = (4x)²+2(4x)(7y)+(7y)²
16x²+56xy+49y²
c) (6 - 5a)² = (6)²+2(6)(5a)+(5a)² = 36+60a+25a²
25a²+60a+36
Bom estudo ✨
30/06
![Ver imagem GLAUCIACKLESSPAA44T](https://pt-static.z-dn.net/files/d01/ea70e41b4491118ca384b367b5c2a057.jpg)
a) (2x + 3)² = (2x)²+2(2x)(3)+(3)² = 4x²+12x+9
b) (4x + 7y)² = (4x)²+2(4x)(7y)+(7y)²
16x²+56xy+49y²
c) (6 - 5a)² = (6)²+2(6)(5a)+(5a)² = 36+60a+25a²
25a²+60a+36
30/06